Evidence summary of lifestyle interventions in adults with metabolic dysfunction-associated steatotic liver disease - Chen, Mei-jing; Chen, Ying; Lin, Jin-qing; Hu, Rong; Liu, Dun; Chen, Jing-yi; Li, Ka; Jiang, Xiao-ying (Frontiers in Nutrition, 2025)
Objective: In this study, our objective was to provide practice recommendations by thoroughly examining lifestyle interventions for adults diagnosed with metabolic dysfunction-associated steatotic liver disease (MASLD). This was achieved through a systematic review of the literature, specifically focusing on lifestyle modification interventions in adults with MASLD. Methods: The PIPOST (Population, Intervention, Professional, Outcome, Setting, and Type of evidence) framework was used to identify the questions for summarizing evidence. Utilizing the 6S model for the hierarchy of evidence, a computerized search was conducted to retrieve articles pertaining to lifestyle interventions for adults with MASLD from websites such as the UpToDate Clinical Advisor, BMJ Best Practice, JBI Library, Cochrane Library, International Guidelines Library, and PubMed, among others. The available research included clinical decisions, clinical practice guidelines, evidence summaries, systematic evaluation, expert consensus, and expert opinions. Two researchers independently evaluated the methodology of the studies, and evidence was subsequently extracted and grouped thematically. Our review encompassed publications from January 2018 to March 2023. Results: A total of 26 publications were identified for the final review, consisting of 7 guidelines, 9 systematic evaluations, and 10 expert consensuses/opinions. From these sources, we derived six themes of evidence: intervention modalities, diet management, exercise management, weight loss management, personalized management, and multidisciplinary collaboration. Conclusion: In the management of adults with MASLD, healthcare professionals should embrace a multidisciplinary team approach, adhere to the best available evidence, and develop structured and personalized interventions based on the best evidence for lifestyle modifications.